Making Sense of Wisdom Management - Peter Müürsepp (International Journal for Applied Information Management, 2021)
An effective manager has to be wise. The paper analyzes different approaches to wisdom and makes proposals about how to apply them for making sense of wisdom management. The focus of the paper, however, is the relationship between wise management and wise leadership. At the basis of a definite understanding of knowledge management, we give the main reasons why wisdom is crucial for effective leadership, especially in self-organizing organizations. Practice is crucial but the basic human faculties of morality and creativity have to be accounted for as well.